ANALISIS RASIO KEUANGAN SEBAGAI ALAT PENGUKUR KINERJA KOPERASI MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA - Isroah, Isroah (Jurnal Pendidikan Akuntansi Indonesia, 2014)
This research had a purpose to get the information about the performance of KOPMA State University of Yogyakarta from the perspective of : level of liquidity from both every division and general, level of solvability from both every dividion and general, and level of rentability from both every division and general. This research was a descriptive research by analizing the data from year 2001 to year 2005 which consist of (1) current ratio, (2) asset turn over, (3) total assets to total debt ration, (4) equity to debt ratio, (5) renability, (6) return on assets and (7) profitability. The result showed that the division of mini market got a loss Rp44.786.312,00 in 2004 and Rp 54.951.190 in 2005. The division of cafe 1 got a loss Rp3.305.297 in 2005. The division of photocopy got a loss Rp20.674.916 in 2005. The ratio analysis showed that : (1) current ratio : 184,48 %, 152,3 %, 189,12 %, 179,83 % and 150,85 % with the average 171,32 % showed that the liquidity was below the criteria (175 %). (2) Asset turn over : 7.1 x, 6.2 x, 4.3 x and 4.6 x with the average 5,66 x showed that the condition was above the criteria. (3) total assets to total debt : 201.03 %, 181.64%, 237,45%, 214.77% , and 166.25% with the average